До питання про визначення поняття та структури злочинності у фінансово-економічній сфері як елемент її кримінологічної характеристики - Маслій, Ігор Володимирович; Маслий, Игорь Владимирович; Maslij, Igor' (My University, 2013)
The concept of crime in financial and economic sphere is grounded and the structure of system of crimes, which should be attributed to the crimes in financial and economic sphere is proposed in the article. There proved that the crime in financial and economic sphere represents a set of acts which are: homogeneous illegal, socially dangerous, selfish, such that cause substantial material damage as a result of infringements of the established order of management of economic processes, economic development of the state, the financial security, for which criminal responsibility is contemplated. There proposed to attribute to such crimes: crimes against property, crimes in sphere of economic activity; other crimes of an economic nature.
Маслій І. В. До питання про визначення поняття та структури злочинності у фінансово-економічній сфері як елемент її кримінологічної характеристики / І. В. Маслій // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 553-561.
Keywords: злочинність; фінансово-економічна сфера; кримінологічна характеристика; преступность; финансово-экономическая сфера; криминологическая характеристика; crime; financial and economic sphere; criminological characteristics